2017
DOI: 10.1038/ncomms15654
|View full text |Cite
|
Sign up to set email alerts
|

Oligolysine-based coating protects DNA nanostructures from low-salt denaturation and nuclease degradation

Abstract: DNA nanostructures have evoked great interest as potential therapeutics and diagnostics due to ease and robustness of programming their shapes, site-specific functionalizations and responsive behaviours. However, their utility in biological fluids can be compromised through denaturation induced by physiological salt concentrations and degradation mediated by nucleases. Here we demonstrate that DNA nanostructures coated by oligolysines to 0.5:1 N:P (ratio of nitrogen in lysine to phosphorus in DNA), are stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
455
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(478 citation statements)
references
References 33 publications
6
455
0
8
Order By: Relevance
“…[44] Moreover, it has been suggested that the delivery rates could be improved by employing DNA intercalators, [45] by directly incorporating specific proteins into the structures, [46] or by using cationic polymer coating. [47][48][49] For DNA binding and coating purposes, dendrons and dendrimers are ideal polymer structures. [50,51] They are regularly branched synthetic molecules with essentially monodisperse structure [52] and high density of functional groups capable of binding various biomolecules with high affinity through multivalent and multimodal interactions.…”
Section: Doi: 101002/adhm201700692mentioning
confidence: 99%
“…[44] Moreover, it has been suggested that the delivery rates could be improved by employing DNA intercalators, [45] by directly incorporating specific proteins into the structures, [46] or by using cationic polymer coating. [47][48][49] For DNA binding and coating purposes, dendrons and dendrimers are ideal polymer structures. [50,51] They are regularly branched synthetic molecules with essentially monodisperse structure [52] and high density of functional groups capable of binding various biomolecules with high affinity through multivalent and multimodal interactions.…”
Section: Doi: 101002/adhm201700692mentioning
confidence: 99%
“…[7][8][9][10][11] Biomedical applications in particular are often incompatible with the comparatively high (10-20 mm)M g 2+ concentrations required for DNA origami assembly.Onthe other hand, low-Mg 2+ concentration ( 1mm)h as been identified as one of the two most critical parameters that reduce DNAorigami stability in cell culture media. [7,8,11,12,14] These discrepancies could have various origins,s uch as differences in the buffer-exchange methods,buffer conditions, and DNAo rigami designs.I nt his work, we therefore investigate the stability of three DNAorigami nanostructures in as election of low-Mg 2+ buffers using the spin filteringbased buffer-exchange approach established by Linko et al [10] We find that the composition of the buffer plays acritical role in DNAo rigami stability,w hile different DNAo rigami nanostructures show different buffer dependencies.First, we set out to reproduce the results of Linko et al for the three DNAo rigami nanostructures investigated in this work, that is,t he Rothemund triangle, [1] a2 4-helix bundle (24HB), [15] and asix-helix bundle (6HB). [12][13][14] All the more surprising was the discovery that DNAorigami are stable in water for several weeks.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Biomedical applications in particular are often incompatible with the comparatively high (10-20 mm)M g 2+ concentrations required for DNA origami assembly.Onthe other hand, low-Mg 2+ concentration ( 1mm)h as been identified as one of the two most critical parameters that reduce DNAorigami stability in cell culture media. [12][13][14] All the more surprising was the discovery that DNAorigami are stable in water for several weeks. [12][13][14] All the more surprising was the discovery that DNAorigami are stable in water for several weeks.…”
mentioning
confidence: 99%
See 2 more Smart Citations